One-Pot Three Component Cascade Synthesis of Fused Ring Quinazoline-2,4-dione Derivatives Employing Heterocyclic Ketene Aminals as a Versatile Synthone - Yaqub, Muhammad; Arif, Nadia; Perveen, Ruqayia; Batool, Javaria; Tariq Riaz, Muhammad; Yaseen, Muhammad (Asian Journal of Chemistry, 2015)
One-pot three component cascade protocol for the synthesis of quinazoline-2,4-dione derivatives was designed and a series of twenty fused ring quinazoline-2,4-dione derivatives 11a-11j and 12a-12j were synthesized by the reaction of heterocyclic ketene aminal, barbituric acid and benzaldehyde. Structure of all the synthesized quinazoline-2,4-dione derivatives was established on the basis of analytical (C, H, N) and spectroscopic (1H NMR, 13C NMR and mass) data and mechanism for the cascade reaction was proposed.